Analisis Karakteristik Butir Soal Tes Ujian Kenaikan Kelas Pelajaran Matematika dengan Program Iteman - Nisa, Chairun (YASIN, 2022)
This study aims to determine the characteristics of the items on the final semester mathematics exam which consist of reliability, level of difficulty, discriminating power, and distractor functioning. This research is the descriptive research with a quantitative approach. The subjects of this study were students of class X MIA program. The object of this research is the response to the test answers as many as 35 responses. Data collection techniques used tests with research instruments of 30 multiple choice questions. To analyze the characteristics of the items consisting of reliability, level of difficulty, discriminating power, and distractor functions, it was carried out with the help of the ITEMAN program. The results of the analysis show that the average score of item difficulty index is 0.3417 included in the medium category, the average discriminating power of item items is 0.133 in the bad category (cannot distinguish between students' abilities), and reliability index with KR-20 of 0.538 with a fairly consistent category.